المعوقات التي تواجه القطاع الثالث بدولة قطر - المنصور، منيرة; الماوري، أحمد (جامعة قاصدي مرباح ورقلة, 2022)
هدف البحث إلى التعرف على المعوقات التي تواجه عمل القطاع الثالث في دولة قطر، تم استخدام المنهج الوصفي التحليلي حيث تم جمع المعلومات من خلال مراجعة وتحليل الأدبيات والوثائق والدراسات السابقة، ومن خلال استمارة استبيان تم توزيعها على عينة من المعنيين في القطاع الثالث في دولة قطر. توصل البحث إلى أن المنظمات غير الحكومية تواجه عدد من المعوقات كضعف مستوى الحوكمة لدى العديد من المنظمات، وغياب التوجه الاستراتيجي وضعف المهارات لدى موظفيها، وكذلك ضعف قدرتها على منح الحوافز المجزية للموظفين مما يحد من قدرتها على جذب الكفاءات وتدريبها والمحافظة عليها، ويتأثر ذلك بضعف مصادر التمويل وتذبذها وعدم توافر موارد ذاتية لأغلب تلك المنظمات. كما تعاني من ضعف الوعي المجتمعي بأهمية وأدوار هذه المنظمات، وضعف التسويق لبرامجه وأنشطته، وكذلك ضعف مستوى المشاركة المجتمعية في أنشطته. وهناك معوقات ترتبط بالجوانب القانونية فهناك العديد من التشريعات التي تنظم عمل المنظمات غير أن بعضها تقيد حركة تلك المنظمات وتضع بعض الإجراءات التي تؤخر إجراءات تأسيس المنظمات من وجهة نظر العينة. إضافة إلى ما سبق، تركيز أغلب الجهات المانحة والمتبرعين على المشاريع الخيرية والإنسانية أكثر من المشاريع التنموية المستدامة، ضعف مستوى التنسيق والتشبيك بين المنظمات غير الحكومية، ووجود بعض الإشكالات المتعلقة بتحويل الأموال نتيجة تبني البنوك إجراءات معقدة في السنوات الأخيرة. كما قدم البحث عدد من التوصيات للتعامل مع تلك التحديات وتعزيز قدرة المنظمات غير الحكومية في قطر على القيام بدور فاعل في التنمية الشاملة.. The aim of the research is to identify the obstacles facing the third sector in the State of Qatar. The descriptive analytical approach was used, where information was collected through reviewing and analyzing the literature, documents, and previous studies, and through a questionnaire distributed to a sample of the third sector in the State of Qatar. The research found that NGOs face a number of obstacles, such as the weak level of governance in many organizations, the absence of strategic direction for most of them and the weak skills of their employees, as well as their weak ability to grant rewarding incentives to employees, which limits their ability to attract, train and maintain competencies, this is affected by weak Funding sources and their fluctuation and the lack of self-resources for most of these organizations. It also suffers from weak societal awareness of the importance and roles of these organizations, weak marketing for their programs and activities, as well as a weak level of community participation in its activities. There are obstacles related to the legal aspects, there are many legislations that regulate the work of NGOs, some of them restrict the movement of these organizations and set some procedures that delay the procedures for establishing organizations from the point of view of the sample. In addition to the above, the focus of most donors and donors on charitable and humanitarian projects more than sustainable development projects, the weak level of coordination and networking between NGOs, and the presence of some problems related to transferring funds because of banks adopting complex procedures in recent years. The research also provides several recommendations to deal with these challenges and enhance the ability of NGOs in Qatar to play an active role in comprehensive development.
Keywords: المنظمات غير الحكومية -- السلوك التنظيمي -- التخطيط الاستراتيجي -- الكفاءات البشرية -- الخدمة الاجتماعية